Unusual repertoire of vocalizations in the BTBR T+tf/J mouse model of autism. - Maria Luisa Scattoni; Shruti U Gandhy; Laura Ricceri; Jacqueline N Crawley (PLoS ONE)
BTBR T+ tf/J (BTBR) is an inbred mouse strain that displays social abnormalities and repetitive behaviors analogous to the first and third diagnostic symptoms of autism. Here we investigate ultrasonic vocalizations in BTBR, to address the second diagnostic symptom of autism, communication deficits. As compared to the commonly used C57BL/6J (B6) strain, BTBR pups called more loudly and more frequently when separated from their mothers and siblings. Detailed analysis of ten categories of calls revealed an unusual pattern in BTBR as compared to B6. BTBR emitted high levels of harmonics, two-syllable, and composite calls, but minimal numbers of chevron-shaped syllables, upward, downward, and short calls. Because body weights were higher in BTBR than B6 pups, one possible explanation was that larger thoracic size was responsible for the louder calls and different distribution of syllable categories. To test this possibility, we recorded separation calls from FVB/NJ, a strain with body weights similar to BTBR, and 129X1/SvJ, a strain with body weights similar to B6. BTBR remained the outlier on number of calls, displaying low numbers of complex, upward, chevron, short, and frequency steps calls, along with high harmonics and composites. Further, developmental milestones and growth rates were accelerated in BTBR, indicating an unusual neurodevelopmental trajectory. Overall, our findings demonstrate strain-specific patterns of ultrasonic calls that may represent different lexicons, or innate variations in complex vocal repertoires, in genetically distinct strains of mice. Particularly intriguing is the unusual pattern of vocalizations and the more frequent, loud harmonics evident in the BTBR mouse model of autism that may resemble the atypical vocalizations seen in some autistic infants.